Words words words - Sreenivasan, T.P. (Delhi, 2008)
Words, Words, Words: Adventures in Diplomacy is more than just a memoir. It is diplomatic history, a meticulously recorded account of the variety of bilateral and multilateral diplomatic negotiations in which T.P. Sreenivasan was involved.
Keywords: Biography-T P Sreenivasan